2013
DOI: 10.1016/j.jaci.2013.08.046
|View full text |Cite|
|
Sign up to set email alerts
|

Tmem79/Matt is the matted mouse gene and is a predisposing gene for atopic dermatitis in human subjects

Abstract: BackgroundAtopic dermatitis (AD) is a major inflammatory condition of the skin caused by inherited skin barrier deficiency, with mutations in the filaggrin gene predisposing to development of AD. Support for barrier deficiency initiating AD came from flaky tail mice, which have a frameshift mutation in Flg and also carry an unknown gene, matted, causing a matted hair phenotype.ObjectiveWe sought to identify the matted mutant gene in mice and further define whether mutations in the human gene were associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
177
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(189 citation statements)
references
References 32 publications
(52 reference statements)
5
177
0
7
Order By: Relevance
“…In the flaky tail mouse, which has a spontaneous mutation in FLG (similar to the mutations found in subjects with IV) and a matted tail mutation (Tmem79/matt) investigators have observed a reduction in occludin (at both mRNA and protein level). 103 These investigators also observed reductions in occludin (mRNA and protein levels) in HaCaT cells transfected with FLG-siRNA and highlighted that loricrin and the silent mating type information regulation 2 homolog 1 (SIRT1) might be part of the signaling pathway that links FLG and occludin. 104 However, it cannot be ruled out that the Tmem79/matt mutation may contribute to changes of occludin in the flaky tail mouse.…”
Section: Tj Abnormalities In Human Skin Disordersmentioning
confidence: 97%
“…In the flaky tail mouse, which has a spontaneous mutation in FLG (similar to the mutations found in subjects with IV) and a matted tail mutation (Tmem79/matt) investigators have observed a reduction in occludin (at both mRNA and protein level). 103 These investigators also observed reductions in occludin (mRNA and protein levels) in HaCaT cells transfected with FLG-siRNA and highlighted that loricrin and the silent mating type information regulation 2 homolog 1 (SIRT1) might be part of the signaling pathway that links FLG and occludin. 104 However, it cannot be ruled out that the Tmem79/matt mutation may contribute to changes of occludin in the flaky tail mouse.…”
Section: Tj Abnormalities In Human Skin Disordersmentioning
confidence: 97%
“…More recently, cohort studies investigating mutations of the filaggrin gene in adults and children, have demonstrated differences between ethnic groups and in responsiveness to treatment (Margolis et al, 2012). Whilst further gene polymorphisms have been linked to abnormal immune responses in AE (Saunders et al, 2013). Ultimately eczematous skin is unable to provide the protective barrier function essential for health.…”
Section: Atopic Eczema and Skin Barrier Functionmentioning
confidence: 99%
“…It was originally thought that the filaggrin deficiency in Flaky Tail mice explained the propensity of these mice to develop AD. Surprisingly, the derivation of genetically engineered filaggrin-deficient mice that were free of the ma gene mutation, were found to display impaired barrier function but to lack the propensity to spontaneously develop eczema (37,38). The matted phenotype in flaky tail mice was found to be due to a loss-of-function mutation in the Tmem79 gene.…”
Section: Complex Causes Of Epithelial Skin Barrier Dysfunction In Admentioning
confidence: 99%
“…Interestingly, Tmem79 encodes lamellar granules that are required for processing of filaggin, lipids, proteases and antimicrobial peptides (22). Saunders et al (37) has also found that a single nucleotide polymorphism in the human TMEM79 gene confers a significant risk for AD in humans, even when controlling for the effect of FLG mutations, suggesting both genes are involved in AD and the need for genegene interactions.…”
Section: Complex Causes Of Epithelial Skin Barrier Dysfunction In Admentioning
confidence: 99%